Insurtech Adoption in Bangladesh: Challenges and Solutions to Overcome Adoption Barriers - Saeed, Maryam; Arshad, Noman (International Journal of Islamic Economics and Governance, 2024)
The idea of insurance was discovered several millennia before Christ (BC). In the second and third millennia BC, traders from China and Babylonia practiced shifting or dispersing risks. Today, insurance is the foundation of the economy, but expanding its penetration is difficult in emerging nations. The fourth insurance industry revolution in the developed world was sparked by the recent advent of Blockchain, IoT, Big Data, and InsurTech. In order to boost insurance coverage in Bangladesh, this study examines the problems with and potential solutions to InsurTech. In order to identify the themes and factors pertaining to problems and solutions in implementing InsurTech in Bangladesh insurance business, this study used a systematic literature review, a rigorous, methodical, and structured process used to gather, evaluate, and synthesize all relevant research on a specific topic. In order to find pertinent material from Google Scholar, a number of keywords were employed. The filtered studies were examined based on inclusion and exclusion standards. This report outlined many obstacles to InsurTech adoption in the Bangladesh insurance sector as well as potential remedies. The proposals could help policymakers improve the insurance industry service delivery.